Description of HbA1c Levels in Fatty Liver Disease Patients in a West Jakarta Private Hospital in 2018-2019 - Chandra, Steven Junius; Gunawan, Paskalis Andrew (International Journal of Public Health Excellence (IJPHE), 2024)
Fatty liver disease is a chronic disease that is very often found in the community and is often called "silent" liver disease because there are no specific symptoms in patients. The incidence of fatty liver disease in Indonesia is quite high by 30 percent and this disease can develop into liver cirrhosis. The high incidence of fatty liver disease can be caused by various factors such as obesity, dyslipidemia, hypertension, unhealthy lifestyles and insulin resistance. Insulin resistance can be characterized by an increase in HbA1c levels in the blood. This study aims to determine the description of HbA1c levels in patients with fatty liver disease. This research is an observational descriptive study using a cross-sectional approach by using medical record data of fatty liver disease patients who have been on radiologic examination and doing HbA1c examination. Fatty liver disease affects more male sex groups by 55.4 percent, with the most age range at 51-60 years by 34.9 percent. Diabetes HbA1c levels (59%) are more than prediabetes (25.3%) and normal HbA1c levels (15.7%). Abnormal HbA1c levels (prediabetes and diabetes) were found to be higher in men (47 % vs 47,3%). The most accompanying diseases in patients with fatty liver disease are diabetes mellitus (51.8%), hypertension (33.7%), dyslipidemia (26.5%), dyspepsia (28.9%), and hyperuricemia (15.7%). Fatty liver disease patients were also found to have metabolic syndrome by 54.2% which was dominated by female sex by 53.3% with 91.1% having 3 components of metabolic syndrome and 8.9% having 4 components of metabolic syndrome